EVALUASI KEMAMPUAN MAHASISWA PPL II JURUSAN PGMI FAKULTAS TARBIYAH DAN KEGURUAN TAHUN 2014 - Siti Shalihah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2015)
Educator is one of the spearheads educational successes, thus an educator must have various competencies to be able to perform the task well. There are 4 competencies required of an educator that is pedagogical competence, professional competence, personal competence and social competence. Department of Primary Teacher Education and Training (PGMI) in Facuty of Education and Teacher Training Program has a vision that is Superior in creating Islamic Primary Teachers are professional, competitive and noble in 2019 in Kalimantan. Curriculum applied in the study program in primary refers to the achievement of the vision and mission, the one course that is mandatory for all students is Field Experience Practice. During the activities Field Experience Practice (PPL) in primary, PGMI students are placed in Madrasah Ibtidaiyah predetermined (Banjarmasin and Banjar district). The length of time students are in school less than two months. The students receive guidance and direction from supervisors (in primary lecturer who has been appointed by the Dean) and teachers from the school officials that they placed. Based on the author’s observation as long as as supervisor PPL II in the public and private Islamic primary schools in Banjarmasin, found that there are still some prospective students teachers who do not have sufficient ability in teaching practice, it can be seen from the lack of learning materials mastery and attitudes that still nervous during teaching practice. In the administration and interaction capabilities, they still have low ability. Based on this evaluation, this research conducted on the ability of students in PPL II teacher education and training (PGMI) program in 2014.